LISTENING TO THE GROANING OF MOTHER EARTH. A CHALLENGE AND AN INVITATION TO MOVE BEYOND ECOLOGY, THROUGH ECOFILIA TO ECOSOPHY – THE NECESSITY FOR A RELEVANT SPIRITUALITY TODAY (Analele Universității București.Filosofie, 2025)
All over the world there is a great concern about Global Warming, migration, wars, poverty, inhumanity, etc. In addition, there is a great concern about Mother Earth as it is being exploited for the sake of profit for a few, and denying opportunities and necessities to the vast majority. In this paper our concern is very much similar because, if we have to build up a relevant spirituality it should be in this context eco-centred which also means humanity-centred. Perhaps, the rich of the Earth have become too selfish that their humaneness seems to have disappeared, and believe only in manipulation and exploitation, and Mother Earth is the greatest victim, which in turn affects the whole humanity. Hence, as Raimon Panikkar says an Ecology which is a pure science is not enough, but we need Ecofilia (friendship with the Earth) and Ecosophy (wisdom of the Earth); we need to learn from the wisdom of Mother Earth, which is sadly lacking today. The effects of the great exploitative wonder Globalization have been disastrous, especially for the developing and underdeveloped nations, and rich countries made use of it for economic colonisation, thus bringing a big majority under thorough economic exploitation. It is here that a new counter-culture and a thoroughly radical spirituality need to evolve, and if need be on the basis of a revolution. We need prophets of such spirituality who will denounce the existing exploitative structures and announce the coming a new society established in peace, justice, and harmony – a new Heaven and a new Earth. The sad fact is that such prophets are extremely lacking being afraid of the ruling parties they do not want to risk their lives. We shall not be proclaimers of doom but prophets and proclaimers of hope that a new society can be built through our commitment to justice, equality, and liberty. Let us take up this mission.